Determinants of Cash Holding: A Study on Manufacturing Companies Listed on the Indonesian Stock Exchange from 2018 to 2021 - Khoirul Hikmah; Puri Prastiwi; Diana Anggraini Kusumawati (AIBPM Publisher, 2025)
This research analyzes the influence of COVID-19, leverage, growth opportunity, net working capital (NWC), dividend, and profitability toward cash holding. The population used is all manufacturing companies recorded on the Indonesian Stock Exchange (IDX) for 2018- 2021. Purposive sampling combined with non-probability sampling was used to determine the research sample, which consisted of 69 manufacturing companies. The research hypothesis was tested using the panel data regression analysis method, namely the Random Impact Model. The research results show that COVID-19, growth opportunity, leverage, NWC, dividend, and profitability impact cash holding. At the same time, it was partially found that COVID-19 had an impact on cash holding, leverage had a significant adverse effect on cash holding, growth opportunity had a negative impact on cash holding, NWC and dividends had an insignificant negative impact on cash holding, and profitability has no significant favorable influence on cash holding. Leverage has a substantial detrimental effect on cash holdings, which suggests that businesses with high levels of leverage are at risk of having liquidity issues. Policymakers may consider providing guidelines or support mechanisms for manufacturing firms to strengthen their financial resilience during uncertain periods